Not the End of the World - McCaughrean G. Geraldine (Oxford, Oxford University Press, 2005)
Everyone knows the story of the flood, the men God chose to survive and the animals that went in two by two. But what about the others that sailed on the Ark - the women and the children? This adventure story asks what it was really like when the heavens opened and the world drowned - and what might have happened in the days that followed.